Glutamate‐ammonia ligase and reduction of G0 population in PANC‐1 cells. Issue 2 (17th December 2012) - Choi, Jong‐Ho; Lim, Key‐Hwan; Park, Eunmi; Kim, Ji‐Young; Choi, Young‐Kil; Baek, Kwang‐Hyun
Abstract In our previous study, we screened and isolated genes that were up‐regulated after partial pancreatectomy using transcriptomic analysis and glutamate‐ammonia ligase (GLUL) was selected for further study based on its effect on differentiation and proliferation. In the immunohistochemical analysis, GLUL was highly up‐regulated in the acinar cells and the ductal cells in the pancreas damaged through partial pancreatectomy. Overexpression of GLUL enhanced the proliferation of PANC‐1 cells and INS‐1 cells. GLUL overexpression shifted the major population of PANC‐1 cells from the G0/G1 phase to G2/M phase. In the double thymidine blocking analysis, similar cycle duration was observed between mock cells and GLUL‐overexpressing cells while GLUL‐overexpressing cells were partially resistant to thymidine blocking. In the FACS analysis of cells stained with Pyronin Y and Hoechst 33342, GLUL‐overexpressing cells showed lower population of cells in the G0‐quiescent phase than mock cells (5–12%). In addition, GLUL‐overexpressing cells had high activation levels of AKT, ERK1/2, JNK, PCNA, c‐FOS, and P70S6K in PANC‐1 cells. Taken together, these results suggest that GLUL contributes to pancreatic regeneration. J. Cell. Biochem. 114: 303–313, 2013. © 2012 Wiley Periodicals, Inc.